If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -6 + -7x = -4 Reorder the terms: -6 + 9x + -7x = -4 Combine like terms: 9x + -7x = 2x -6 + 2x = -4 Solving -6 + 2x = -4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2x = -4 + 6 Combine like terms: -6 + 6 = 0 0 + 2x = -4 + 6 2x = -4 + 6 Combine like terms: -4 + 6 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 70+55+6x-11=180 | | (3x+5y)dx+(14x+6y)dy=0 | | 3x+3=417 | | 0.582y+6-0.33y=8 | | -4n+6n=4n-12 | | 120floz=xqt | | x(9x-9)=(9x+2)(x-1) | | -8(5+k)=104 | | 9x^3-4x=18x^2+8 | | p^2+4p-3=2 | | 10(5x-3)=135 | | 8x+7-6x=2 | | 3(r+6)=54 | | -8(x+5)=-6(x+2) | | 0.3x+2=-0.3x+1 | | -7-9(1-4x)=-20 | | 84+46+5x-10=180 | | 60x+24=.25 | | -100000000x+200000000=0 | | -15-k=8 | | 6a+7=1+6a | | 36p+24=.25 | | x+6+x=-10+4x | | 36+24=.25 | | 5ln(8x)=40 | | 12x+2=-18x+2 | | 82+53+45x=180 | | 893x+10=128 | | 2n-8n=12+n-4n | | 10(x+2)=-(-4-4x)+2x | | 14x-53-32x=72 | | 7x+7=2x+12 |